A comparison of ECG-based home monitoring devices in adults with congenital heart disease. (14th October 2021) - Bokma, J P; Pengel, L K D; Robbers-Visser, D; Groenink, M; Boekholdt, S M; Bouma, B J
Abstract: Background: Various devices are available for electrocardiogram (ECG) based home monitoring and could facilitate early detection of arrhythmias in adult congenital heart disease (ACHD). However, the diagnostic accuracy of these devices in ACHD is unknown. Purpose: We aimed to determine the accuracy of different ECG-based devices compared to the standard 12-lead ECG in ACHD. Methods: We performed a single-center, prospective, cross-sectional study in consecutive ACHD patients. We determined diagnostic accuracy of the Withings Scanwatch (lead I), Eko DUO (precordial ECG) and Kardia 6L (six leads) compared to the 12-lead ECG on several parameters: 1) automatic atrial fibrillation (AF) detection, 2) QRS-morphology assessment (simplified into normal (<120ms), right bundle branch block (>120ms) or other wide complexes (>120ms)), and 3) conduction times (PR, QRS, QTc time). All 12-lead and device ECGs were evaluated by a single observer. Results: A total of 176 patients (54% male, age 40±16.6 years, 24% severe ACHD, 84% previous correction, six patients with AF) enrolled in the study. The Withings algorithm classified only 5% of ECGs as inconclusive compared to 31% of Kardia 6L (p<0.001). Both devices had comparable sensitivity and specificity (Withings: 100% and 100% vs. Kardia 6L: 100% and 97%) in ECGs that were classified by the algorithm. On Kardia 6L, QRS morphology was correctly classified more frequently (90%) compared to EKO duo (84%) (p=0.03) and identified the P-wave more frequently (85%) (p<0.001 compared to both). Evaluation of all ECG-based devices underestimated QTc and QRS duration compared to the 12L ECG (p<0.01). Withings (49%) more frequently over- or underestimated QTc-interval by more than 40msec compared to Eko DUO (30%) and Kardia 6L (26%) (p<0.001 for both). Overall, ECG quality of Withings Scanwatch was rated worse compared to Kardia 6L and EKO duo (p<0.001 for both). Conclusions: This is the first study to examine diagnostic accuracy of different ECG-based devices in ACHD. Overall, Withings Scanwatch may be the most practical choice for continuous AF screening while Kardia 6L could be preferred to accurately capture symptomatic palpitations. These findings can inform both patients and caregivers for optimal choice of home monitoring. FUNDunding Acknowledgement: Type of funding sources: None.